Concise pathology - Chandrasoma, Para (Appleton & Lange, 1998)
With an emphasis on diseases most important to clinical practice, the third edition of this resource presents an understanding of pathogenesis as the foundation of clinical knowledge. Divided into general and systemic pathology, the tightly focused discussion is enhanced by four pages of pathology specimens displayed in true color. This new feature makes this an ideal reference for the classroom and the laboratory.